The Challenges of Writing Academic Article: Voices of Higher Education Students - Violintikha Harmawan; Vischa Mansyera Pratama; Rahmi Fadilah (Universitas Negeri Padang, 2023)
Academic writing is commonly characterized as scientific writing which is portrayed as an organized research practiced and utilized by researchers at higher education level. The purpose of the study is to investigate the challenges faced by students in the process of writing an academic article. This present study is a qualitative research that explores the voices of three higher education students toward challenges in writing an academic article. The data were analyzed descriptively and were divided into three big themes. The findings showed that the main challenges faced by students during the process of writing an academic article are grammatical structure, paraphrasing and organizing ideas. It is suggested that the teachers’ or lectures’ roles and support in process of writing is very important in order to build students’ motivation.